A review on CO2 capture via nitrogen-doped porous polymers and catalytic conversion as a feedstock for fuels. (20th December 2020) - Mukhtar, Ahmad; Saqib, Sidra; Mellon, Nurhayati Binti; Rafiq, Sikander; Babar, Muhammad; Ullah, Sami; Muhammad, Nawshad; Khan, Asim Laeeq; Ayoub, Muhammad; Ibrahim, Muhammad; Maqsood, Khuram; Bustam, Mohamad Azmi; et al.
Abstract: The minimisation of the continuously enhancing level of the CO2 released to the atmosphere is one of the most significant issues faced by the scientific community. Rigorous research efforts have been carried out for the development of sustainable and cost-effective nitrogen-rich porous adsorbent materials for energy-efficient and enhanced polar gas separation, i.e. pre-combustion and post-combustion CO2 capture. Among different porous adsorbent materials, the covalent triazine frameworks (CTFs) are found to be remarkable candidates for CO2 capturing because of their facile and scalable synthesis, high surface area, permanent porosity, structural tunability, synthetic diversity, low density, high hydrothermal and physicochemical stability. A contextual overview is described on the key challenges in CO2 sequestration, parameters consideration for the design of CO2 selective porous adsorbents, evaluation criteria for the adsorption processes, assessment criteria for the selection of suitable adsorption configuration, and the factors influencing the CO2 adsorption capacity. This review comprises deep critical scrutiny of the current investigation and development on Triazine-, benzimidazole-, and triazole-based COPs with improved CO2 storage capacities. The conversion of CO2 into useful products including the carbon monoxide (CO), methane (CH4 ), methanol (CH3 OH), and other products including the hydrocarbons has been critically reviewed by using the heterogeneous catalysis. Finally, a concise conclusion and recommendation section are presented indicating that the area of Triazine-, benzimidazole-, and triazole-based COPs for CO2 capture needs more attention to synthesise the next-generation materials for real-time applications. Graphical abstract: Image 1 Highlights: Global scenario on CO2 and GHGs emission are reported. Adsorbent design parameters, evaluation and assessment criteria discussed. Factors influencing the CO2 adsorption capacity are discussed. Triazine-, benzimidazole-, and triazole-based COPs for CO2 adsorption reported. Heterogenous Catalysts for CO2 conversion to useful products are critically reviewed.